Pemanfaatan Tokoko.id Dalam Memasarkan Produk Handcraft - Ria Rismayati; Phyta Rahima (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The use of e-commerce applications which are currently in great demand by business activists has been very helpful in marketing products, especially those engaged in trade because e-commerce is able to expand the market thereby increasing the number of sales of the products being marketed. To see the level of effectiveness of e-commerce, the authors conducted a service activity entitled Utilization of Tokoko.id in marketing Handcraft products. Tokoko is an application to make selling easier and fasterby simply sharing a link in the Instagram bio that is owned by the Tokoko id producer connected to the WhatsApp application to communicate with customers. Handcraft or commonly known as handicraft is the skill to create a product or item that is done by hand and has a function of use or beauty and has a selling value,so the handicraft business opportunity is quite promising. The use of the tokoko application is very helpful in selling this handcraft. The stages/methods used in this activity are; Planning, Preparation, Implementation and Evaluation and conclusion. Based on the results obtained, it can be said that Tokoko.id is quite helpful in the sales process, especially in the field of promotion